Crime Deterrence: Evidence From the London 2011 Riots. (May 2014) - Bell, Brian; Jaitman, Laura; Machin, Stephen
<x xml:space="preserve">Abstract</x> Significant riots occurred in London in August 2011. The riots took place in highly localised geographical areas, with crime going up hugely in the affected sub‐wards. The criminal justice response was to make sentencing for rioters much more severe. We show a significant drop in riot crimes across London in the six months after the riots, consistent with a deterrence effect from the tougher sentencing. More evidence of general deterrence comes from the observation that crime also fell in the post‐riot aftermath in areas where rioting did not take place.